Enhancing a Workforce: A Review of State‐Level Processes for Advancing Community Health Worker Development. (15th September 2021) - Shantharam, Sharada; Fulmer, Erika; Moeti, Refilwe; Barbero, Colleen; White, Allison; Bhatt, Ami
Abstract : Research Objective: Community health workers (CHWs) are a public health workforce essential to preventing and managing cardiovascular and other chronic diseases in the United States. CHWs are trusted members of the communities they serve, working to assure health equity by reducing barriers to and increasing opportunities for cardiovascular disease prevention and management. Although there has been widespread interest in supporting, enhancing, and stimulating demand for the CHW workforce, there is limited literature describing processes needed to do so. This study sought to identify and describe state‐level processes and related elements critical to CHW workforce development. Study Design: During 2017–2020, using process theory, the Centers for Disease Control and Prevention (CDC) and external partners conducted a multi‐phase study to explore state‐level CHW workforce development processes. The study team engaged subject matter experts, conducted key informant interviews, and held focus groups with CHWs, state health department representatives, payers, and CHW employers to develop a conceptual model and complete a case study illustrating the statewide CHW workforce development processes. Additionally, a secondary analysis of over 400 publicly available documents from the 50 US states, Washington, DC, and Puerto Rico refined the model and clarified the process elements (i.e., actors, events, contextual factors, and outputs associated with each process within the conceptual model). Population Studied: This study examined CHW workforce development processes. It included CHWs – also known by a diversity of titles such as promotores de la salud, and community health representatives, and lay health extenders – within the US. Principal Findings: The study identified 12 processes involved in CHW workforce development: leveraging investments in statewide CHW workforce development initiatives; including CHWs in statewide health system changes; developing evidence and tools in support of statewide CHW initiatives; establishing statewide CHW organizations, definitions, standards, and/or policy; supporting statewide CHW organization and leadership; identifying CHWs and employers interested in CHWs statewide; creating statewide training and development opportunities for CHWs and their employers; creating statewide opportunities for proficiency assessment/credentialing to recognize CHWs; assessing statewide employer readiness/support for CHWs; and assessing increased/enhanced statewide CHW employment. Example process elements included multi‐stakeholder CHW coalitions, CHWs being included in Medicaid Managed Care Organizations, state scope of practice laws, and routine monitoring of statewide CHW employment. Conclusions: The processes involved in state‐level CHW workforce development are complex, multi‐faceted, and inter‐related. They involve interconnected stakeholders, facilitators and barriers, outputs, and impacts. Processes are layered and those occurring at the policy‐ or systems‐level serve as a foundation for organizational‐ and community‐level actions, which, in turn, serve to enhance and increase CHW employment. Implications for Policy or Practice: Over recent years, there has been a significant increase in supporting the CHW workforce due to federal‐ and state‐level resources and efforts. Nonetheless, additional work is needed to strengthen and maximize the reach and impact of this important public health workforce. This conceptual model can be used in future planning and evaluation for statewide CHW workforce development initiatives by serving as an empowering tool for CHWs to advance the profession and an educational tool to inform employers on how to support CHWs. Primary Funding Source: Centers for Disease Control and Prevention.